The relevance of studying the problem of garbage and its recycling in large cities (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
Today, urban development is developing at a rapid pace, economic growth and lifestyle changes lead to an increase in cities and an increase in the urban population, which in turn leads to an increase and accumulation of solid household waste in these cities. Solid sweat waste is probably one of the most urgent problems of mankind, especially nowadays. We encounter garbage all the time, at home at work, walking down the street, walking in the park, in a word, everywhere. All this garbage has a very strong effect on us, it affects both physical health, worsening it, and psychological health. All this is an integral part of our life, and people have even learned to deal with this problem. But not everything is as simple as it might seem at first glance. Although it seems to me that the problem is not in the garbage itself, but in how people treat it.For example, consider such a phenomenon as "Waste dumps" or "Garbage landfills", which today cause considerable concern. First of all, this is a negative impact on ecology, primarily soil pollution around the landfill, groundwater pollution, which entails a problem with fresh water. Another important aspect is air pollution and an unpleasant smell that can spread for many kilometers. A large part of the population claims that all waste problems can be solved by recycling. Despite this, landfills continue to be the most common form of waste disposal worldwide. There is also a common belief that landfill is an economical means of waste disposal. Yes, it is definitely the cheapest and easiest way to get rid of waste, but is such savings worth the environmental problems that will arise in the future.
Keywords: architecture; urban planning; garbage; dumps; landfills; ecology; pollution; recycling; utilization